2009
DOI: 10.4161/oxim.2.2.8493
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Degenerative Disorders: Antioxidative Activity, Total Phenols, Flavonoids, Ascorbic Acid, β‐Carotene and β‐Tocopherol in Aloe vera

Abstract: In order to demonstrate whether the known biological effects of Aloe vera (L.) Burm. fil. could correlate with the antioxidant activity of the plant, the antioxidant activity of the aqueous leaf extract was investigated. The present study demonstrated that the aqueous extract from A. vera leaves contained naturally occuring antioxidant components, including total phenols, flavonoids, ascorbic acid, β-carotene and α-tocopherol. The extract exhibited inhibitory capacity against Fe3+/ascorbic acid induced phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 60 publications
4
83
1
2
Order By: Relevance
“…The DPPH free-radical-scavenging activities of resveratrol, pterostilbene, piceatannol, their β-glucosides, resveratrol 3-maltoside, and resveratrol 4′-β-maltoside were determined as follows. 19,20) DPPH was dissolved in methanol (MeOH) (0.15 mM). The sample solutions were prepared by dissolving each compound in MeOH (2 mM).…”
Section: Analysesmentioning
confidence: 99%
“…The DPPH free-radical-scavenging activities of resveratrol, pterostilbene, piceatannol, their β-glucosides, resveratrol 3-maltoside, and resveratrol 4′-β-maltoside were determined as follows. 19,20) DPPH was dissolved in methanol (MeOH) (0.15 mM). The sample solutions were prepared by dissolving each compound in MeOH (2 mM).…”
Section: Analysesmentioning
confidence: 99%
“…Cinnamoyl, p-coumaroyl, feruloyl, caffeoyl aloesin [159]. Phenols, flavonoids, ascorbic acid, β-carotene and α-tocopherol [160]. Mannose polymers with some glucose and other sugars; mainly acemannan, glycoproteins, enzymes, amino acids, vitamins, and minerals [161].…”
mentioning
confidence: 99%
“…Moreover, therapeutic activity may be associated with substance mixture coming from ethyl acetate extraction of Aloe vera which demonstrated concentration-dependent ROS scavenging action. It is accepted that antioxidant activity of Aloe vera is related to the presence of phenolic compounds in its extracts (Ozsoy et al, 2009). This effect is also regarded the most beneficial therapeutic activity of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera is used both internally and externally on humans in a form of alternative medicine as well as in the home in first aid. It has been shown that Aloe vera expresses wound-and burn-healing effects and shows immunomodulatory, anti-inflammatory, antiparasitic, UV protective, antioxidant, antiviral, antitumor and antidiabetic activities (Lee et al, 2000;Choi & Chung, 2003;Sarkar et al, 2005;Yoo et al, 2008;Kigondu et al, 2009;Ozsoy et al, 2009). Telefo et al (1998Telefo et al ( , 2002Telefo et al ( , 2004) also demonstrated the effect of Aloe vera on the reproductive system in rats where the plant extract regulated the steroidogenesis and hormone levels, menstrual cycle, ovarian and uterine weight and was used to treat dysmenorrhea or infertility.…”
Section: Introductionmentioning
confidence: 99%